Recurrent Thymic Carcinoma Treated With Median Sternotomy, Innominate Vein Replacement for Superior Vena Cava, and Iodide Implantation: A Case Report and Review of the Literature - Zhong‐zheng Chen; Wen‐dong Qu; Xing‐shu Zhang; Yong‐xiang Song (Cancer Reports)
ABSTRACT Background Neuroendocrine tumors of the thymus (NETT) are rare and malignant tumors that arise in the anterior mediastinum. These tumors can exhibit aggressive behavior and may involve surrounding critical structures, such as the superior vena cava. This case contributes to the literature by presenting a recurrent thymic carcinoma with invasion of major blood vessels, including the superior vena cava, and the complexities involved in its surgical management. Case A 51‐year‐old male with no significant medical history presented with eyelid edema and a mediastinal mass. Diagnostic imaging, including positron emission tomography/computed tomography (PET/CT), revealed a malignant anterior mediastinal mass with possible metastasis. The patient underwent thoracoscopic resection of the tumor and wedge resection of the left upper lobe of the lung. Postoperative pathology confirmed a neuroendocrine carcinoma (G3), staged as Masaoka IVa. Despite aggressive surgery, the patient developed recurrent metastasis involving mediastinal lymph nodes and the superior vena cava. The patient underwent complex surgery involving vascular replacement, pericardial resection, and superior vena cava reconstruction, followed by adjuvant chemotherapy, radiotherapy, and immunotherapy. Conclusion This case highlights the challenges of managing advanced NETT, particularly with invasion of major vascular structures. It emphasizes the importance of early diagnosis, complete surgical resection, and tailored adjuvant therapies, including chemotherapy, radiotherapy, and immunotherapy, to improve survival outcomes. The lessons learned from this case contribute to refining treatment strategies for similar cases, advocating for aggressive surgical approaches and the potential benefit of novel therapeutic agents in the management of advanced NETT.